The National Research Biobanking Guidelines - Uganda National Council for Science and Technology (Uganda National Council for Science and Technology, 2021)
The National Research Biobanking Guidelines provide Uganda's national framework for the establishment, certification, governance, operation, and regulation of biobanks that collect, process, store, share, and manage biological specimens and their associated data. The guidelines apply across multiple sectors, including health, agriculture, veterinary sciences, environmental sciences, forensic science, wildlife, aquatic sciences, and education. They establish standards for ethical and legal compliance, informed consent, community engagement, quality management, biosafety, biosecurity, specimen transportation, records management, data protection, disaster preparedness, and collaborative research. The document also defines the roles and responsibilities of the Uganda National Council for Science and Technology (UNCST), Institutional Biosafety Committees, biobank custodians, researchers, and other stakeholders in ensuring responsible biobanking practices. Ultimately, the guidelines seek to safeguard the rights of sample donors, promote high-quality research, strengthen national biobanking capacity, facilitate scientific collaboration, and ensure that biological materials and associated data are managed with integrity, transparency, accountability, and in accordance with national and international standards.
Keywords: Biobanking; Guidelines; Uganda